Reliability of three timing systems used to time short on ice- skating sprints in ice hockey players - Bond, C. W.; Willaert, E. M.; Rudningen, K. E.; Noonan, B. C. (The Journal of Strength and Conditioning Research, 2017)
Speed and acceleration are highly valued in ice hockey and frequently assessed using timing systems. Coaches must use reliable timing systems to assess these attributes, but many systems have not been thoroughly evaluated and the required number of sprint repetitions to obtain the coach's desired degree of reliability for a system may be impractical. This study aimed to compare the reliability of a single photocell (PC), a single laser with a microprocessor (LA), and a digital video camera (VC); and in doing so, evaluate the influence of completing additional sprint repetitions on each systems' reliability. We hypothesized that PC and LA would yield different times, have inferior reliability, and require a larger number of sprint repetitions to obtain the same degree of reliability compared with VC. Seventeen male ice hockey players completed 5 repetitions of a 9.15 m on ice-skating sprint timed simultaneously by PC, LA, and VC. The times obtained from VC were narrowly distributed around the mean compared with PC and LA and resulted in a mean sprint time approximately 0.05 and 0.07 second faster than PC and LA, respectively {PC: 1.74 second (95% confidence interval [1.72-1.76]); LA: 1.76 second [1.74-1.78]; VC: 1.69 second [1.67-1.70]}. When 2 sprint repetitions were completed, PC and LA typical error (TE) and smallest worthwhile difference (SWD) were 2.8- and 4.3-fold greater than VC, respectively. As more repetitions were completed, TE and SWD for PC and LA improved but remained approximately 2-fold greater than VC even when 5 repetitions were completed. With a smaller TE and SWD, VC was able to detect smaller "real" changes in a player's sprint performance over time compared with PC and LA.